PENGARUH PENGGUNAAN SERBUK BIJI KELOR (MORINGA OLEIFERA) TERHADAP PENURUNAN KONSENTRASI CU(II) DALAM LIMBAH CAIR BUATAN DENGAN PROSES ADSORPSI - harmin sulistyaning titah (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
Kelor (Moringa oleifera) is a kind of bush plant, which has a number of application potential, started from the leaf till the root. The seeds can produce 4-(alpha-L-rhamnosyloxy)benzyl isothiocyanate compound which can bind Cu(II). Besides, the seed also contains protein with cysteine and methionine components, which can bind Cu(II) from S-H group. In this research, copper adsorption by horse radish seed was measured, using complete powdered seeds (with epidermis skin part) and incomplete seeds (without epidermis). Two sizes of the powdered seed of 35/80 and 80/115 mesh sizes were applied. The initial concentrations of Cu(II) were 0; 0,25; 1; 5; 10 mg/L. The Cu(II) concentrations were analyzed using Atomic Absorption Spectrophotometer. In the batch process, the removal efficiency of Cu(II) was up to 97,07 % at initial concentration of 10 mg/L, using the incomplete seeds of 80/115 mesh size. In a continuous process with a flowrate of 0,5065 ml/minute Cu(II) removal was up to 96,2 %, and the adsorption capacity was 0,000149 mg adsorbate/mg adsorbant.